Development and validation of a measure of quality in playgroups: Playgroups environment rating scale - Russo, V.; Barata, C.; Alexandre, J.; Leitão, C.; Sousa, B. (Frontiers in Education, 2022)
Playgroups are community-based services that bring together young children and their caregivers for the purpose of play and social activities. Preliminary evidence shows that playgroup impacts may be dependent on the quality of the playgroup. However, to date, there is no reliable and valid measure of playgroup quality. In this paper we describe the development and validation of the Playgroup Environment Rating Scale (PERS), a standardized observation measure designed to assess the quality of playgroups. PERS builds on traditional measures used to evaluate the quality of formal settings of early childhood education and care, while proposing to assess dimensions of quality specific to the nature of playgroups, namely complex interactions between several types of participants. After developing and testing the observation measure on 24 playgroup videos, we analyzed the psychometric properties. Results showed that the PERS had good interrater reliability, was internally consistent and shows a good preliminary factor structure. Tests for convergent and criterion-related validity also presented promising results. The process of design guaranteed that the PERS can be applied to different contexts of playgroups and may also be useful for informing service planning and practice. Further national and international validation will help replicate the validity of the scale.